Cloud computing: Does every cloud have a silver lining? - Dela Cruz, Aeson Luiz (Animo Repository, 2014)
Up in the clouds, we go. Ever wondered where pictures uploaded on your Facebook profile are stored? How about files that you keep on your DropBox, that you conveniently access wherever you are and whenever you need them? Perhaps, it is more intriguing to ask where videos you have uploaded in YouTube are being kept. Are you not curious enough to ask why your Google mail can provide additional storage capacity when needed? All the answers to these questions lead us to a single direction—to the clouds.